2015
DOI: 10.1007/s13538-015-0383-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Temperature and Reaction Cycle Number on Atomic Layer Deposition of TiO2 Thin Films Using TiCl4 and H2O Precursors: Correlation Between Material Properties and Process Environment

Abstract: How to citeComplete issue More information about this article Journal's homepage in redalyc.org Scientific Information System Network of Scientific Journals from Latin America, the Caribbean, Spain and Portugal Non-profit academic project, developed under the open access initiative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 51 publications
2
23
1
Order By: Relevance
“…The TiO x films show an excess of oxygen, i.e., x values ranging from 2.13 ± 0.01 to 2.33 ± 0.01, as can be seen in Figure 3. These results differ from those described for thermal ALD TiO 2 films, in which either stoichometric or oxygen-deficient films are obtained [52]. The increase of oxygen content in PEALD TiO 2 films may be related to the higher reactivity of O 2 plasma compared to the water precursor used in thermal ALD.…”
Section: Structure and Morphologycontrasting
confidence: 88%
See 1 more Smart Citation
“…The TiO x films show an excess of oxygen, i.e., x values ranging from 2.13 ± 0.01 to 2.33 ± 0.01, as can be seen in Figure 3. These results differ from those described for thermal ALD TiO 2 films, in which either stoichometric or oxygen-deficient films are obtained [52]. The increase of oxygen content in PEALD TiO 2 films may be related to the higher reactivity of O 2 plasma compared to the water precursor used in thermal ALD.…”
Section: Structure and Morphologycontrasting
confidence: 88%
“…The crystalline condition of pure TiO 2 thin films due to the strong peak at 144 cm −1 is clearly evidenced. On the other hand, for the TiO 2 /Al 2 O 3 nanolaminate, the main peaks of the anatase phase were not observed, and the rutile phase is formed above 500 • C for silicon substrate [28,37,52,53], which suggests that the film is amorphous or partially crystalline. Figure 4b shows the micro-Raman spectra evidencing the shift and the full width at half maximum (FWHM) of the E g peak at 144 cm −1 .…”
Section: Structure and Morphologymentioning
confidence: 94%
“…Certainly, the selection of Ti and O 2 precursors is another important factor due to the different activation kinetics for different precursors. Several works have suggested that the crystallization process is initiated at the temperature range of 165–250°C (Aarik et al, 1995, 2013; Saha et al, 2014; Chiappim et al, 2016). For example, an 11 nm thin anatase TiO 2 film was obtained at deposition temperature of 225°C when TiCl 4 and H 2 O were employed as precursors (Aarik et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…While for Al 2 O 3 films the cycle times were 0.15, 0.75, 0.15 and 0.75 s for the TMA pulse, purge, H 2 O pulse and another purge, respectively. These are optimal cycle time conditions investigated in early studies [29,30,31,32,33,34]. The vapors of TiCl 4 , TMA and H 2 O were led into the reaction chamber from external reservoirs kept with liquid TiCl 4 (99.95 %, Sigma-Aldrich, São Paulo, Brazil), liquid TMA (97%, Sigma-Aldrich) and deionized water at temperature of 21 °C.…”
Section: Methodsmentioning
confidence: 99%